Programa Previne Brasil: uma análise da mudança na atenção básica à saúde em espaços deliberativos do SUS - Mitros, Verônica Maria da Silva (2022)
In November 2019, Previne Brasil was launched, a new funding model for Primary Health Care (PHC) funding within the Unified Health System (SUS). In the context of an economic and political crisis, the proposal for new funding was analyzed as yet another obstacle in guaranteeing the principles of the SUS. Considering that in the Brazilian federative model the main decisions regarding the definition of strategies, monitoring and evaluation of public policies are discussed in deliberative spaces, this work has the general objective: to analyze the change in the Primary Health Care Policy in Brazil, in the period from 2016 to 2020, especially with regard to the decision-making processes at the Tripartite Intermanagers Commission (CIT) and the National Health Council (CNS), which focused on the approval of the Previne Brasil Program. This is a Case Study, where information from the minutes of the CNS meetings, from 2016 to 2020, and the agendas and videos of the CIT Ordinary Meetings, between 2019 and 2020. They were analyzed and entered into ATLAS ti 8 in order to build a chain of evidence according to the analyzed period. Throughout 2019, CIT discussions regarding PHC highlighted several projects that were instituted on the grounds of the need to expand Access and improve the assessment and quality of care. Discussions that were built in order to complement and support the change in funding that occurred at the end of the same year. While at CIT the speeches show agreement, within the scope of the CNS the members comment on the new funding being a result of the reduction of incentives of the tax regime with EC nº 95, with restriction of rights and expansion of underfunding, suggesting and reinforcing the need for revocation of the constitutional amendment and Previne Brasil. The creation of Previne Brasil, in addition to not being a good solution to improve the distribution of resources, the universality of access and the assessment of quality in care, was still instituted in a context of violation of the principles and guidelines of the Unified Health System and without the dialogue and approval of the CNS. As limitations of the study, the method used in this work comprises the CNS from the years 2016 to 2020, however, only the CIT meetings from the years 2019 and 2020 were included, as videos from previous years were not available. For a greater analysis in the period before the change of funding, it would be important to analyze the discussions of the CIT also in the other periods. It is also necessary to investigate the alternatives studied by the actors for financing models